Maternity care providers' involvement in research. (August 2020) - Shiplo, S.; Meaney, S.; O'Donoghue, K.
Abstract: Objective: Despite the widely acknowledged importance of research for improving patient care and outcomes, research in pregnant women is lacking. Many challenges innate to conducting research in pregnant women may discourage maternity care providers from engaging in research. Thus, the current study assessed maternity care providers' involvement in research, their perception of the relevance of research, as well as facilitators and barriers to participating in research. Study Design: A total sample of 145 maternity care providers were recruited from a large tertiary-referral university-based teaching maternity hospital. Maternity care providers included, midwives, nurses, sonographers, consultant obstetricians, and non-consultant hospital doctors. Participants completed a cross-sectional survey between May and October 2018. Results: The present study found that overall, 49.7% of maternity care providers who participated reported never taking part in conducting research. Medical staff were more likely to report being given the opportunity and to have ever conducted research compared to midwives ( p < 0.05). Participants agreed that research is important to maintain the quality of care provided to women (Mean = 4.86/5 in agreeance). However, medical staff were more likely to report understanding research methodology and feeling competent to undertake research compared to midwives (Mean = 3.85 v 3.28, p = 0.002; Mean = 3.56 v 2.60, p < 0.05). Conclusion: The findings suggest future strategies aimed at increased opportunities and additional research training will likely support maternity care providers', specifically midwives, involvement in conducting effective research studies in pregnancy. Such actions hold the potential to contribute research evidence lacking in pregnant women necessary to provide appropriate maternity care.